2011
DOI: 10.1590/s1516-14392011005000084
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic degradation of a resin composite as a function of the curing tip distance and aging

Abstract: The influence of curing tip distance and storage time on the hardness of a composite was evaluated. Composite samples (Filtek Z250) were polymerized at different distances (5, 10, and 15 mm), compared with a control group (0 mm), and stored in distilled water at 37 ° C for 24 hours. The Knoop-hardness of top and bottom surfaces was assessed (25 g/30 s). Specimens were stored in distilled water for 6 and 12 months and were retested. Hardness was found to be negatively influenced by both curing tip distance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This causes the bond between the filler and the matrix to be unstable. 13,32 . This also results in reduced mechanical resistance of the resin when surface degradation occurs, resulting in a rough surface of the restoration material.…”
Section: Discussionmentioning
confidence: 99%
“…This causes the bond between the filler and the matrix to be unstable. 13,32 . This also results in reduced mechanical resistance of the resin when surface degradation occurs, resulting in a rough surface of the restoration material.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons that explain the fact that the experimental groups exhibited different final mass relies on the ability of the polymer network to release unreacted monomers through nanovoids in the material 27 , showing a decrease in mass within a short time of water immersion. Based on a previous study 11 , composite can degrade very differently after water storage and it is influenced by the degree of conversion and the quantity of pendant molecules existing within the polymer network 26 . The quality of the network that forms during polymerization can dictate the extent to which molecular uptake and swelling occur when a polymer is submerged in a solvent 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been found that the curing distance and the immersion time affects surface hardness 11 . The efficiency of polymerization may also influence the composite discoloration, since the amount of residual monomers available to form colored degraded products is reduced in well polymerized composites 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation